2013
DOI: 10.1299/jtst.8.363
|View full text |Cite
|
Sign up to set email alerts
|

Flows of Polymer Melts through Nanopores: Experiments and Modelling

Abstract: The polymer melts flow behaviors through nanopores are investigated by using the nanoporous template wetting technique in our study. The experimental observation indicates that the meniscus rises according to a (time)1/2 law which agrees with the Lucas-Washburn law. Comparing the experimental results with the Lucas-Washburn equation, we also demonstrate that the viscosities of polymer melts decrease in their flows through nanopores and the induced rheological behavior is caused by the nanoconfinement of nanopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
(34 reference statements)
1
6
0
1
Order By: Relevance
“…There have been innumerable theoretical [33][34][35][36][37] and simulation [38][39][40][41][42] studies of polymer nanocomposites over the past twenty years. There have also been several experiments and simulations focusing on Lucas-Washburn-type during capillary flow, [43][44][45][46][47][48][49] however, most of these past studies focused on flow through a capillary tube. Furthermore, previous simulations 49 at the nanoscale have shown quantitative limitations of the Lucas-Washburn relationship in relation to slip flow, where a small modification to the equation is required to regain quantitative consistency.…”
Section: Introductionmentioning
confidence: 99%
“…There have been innumerable theoretical [33][34][35][36][37] and simulation [38][39][40][41][42] studies of polymer nanocomposites over the past twenty years. There have also been several experiments and simulations focusing on Lucas-Washburn-type during capillary flow, [43][44][45][46][47][48][49] however, most of these past studies focused on flow through a capillary tube. Furthermore, previous simulations 49 at the nanoscale have shown quantitative limitations of the Lucas-Washburn relationship in relation to slip flow, where a small modification to the equation is required to regain quantitative consistency.…”
Section: Introductionmentioning
confidence: 99%
“…Although a notable low viscosity was reported for the polymer in the nanochannels in that communication, no influence of reduced dimensions was detected. Apparently, the low dimensionality effects on large-scale dynamics, such as diffusion of chains, are exclusively observed within nanocavities in the range the radius of gyration of the polymer, as reported by Shin et al [228]. They investigated the capillary flow of PS melts along pores of 15 nm and observed a significant enhancement of the chain diffusion, as well as a weak molecular-weight-dependence of the dynamics.…”
Section: Confinement Effects On Rheological Propertiesmentioning
confidence: 63%
“…Once an AAO template is made, nanowires can be fabricated by filling nano-pores with desired material such as metal [41][42][43][44][45][46][47], metal oxide [44,[48][49][50][51][52][53] and polymeric materials [2][3][4][5][6][7][8][9][11][12][13]. To deposit Sample topological features include: (a) thin wall nano-pores with large aspect ratio (e.g., pore depth: diameter >100:1), which is anodized at 1 • C and 60 V for 4 h. (b) thick wall pores with a small pore diameter (e.g.,~50 nm), which is anodized at −3 • C and 140 V for 2 mins.…”
Section: Vacuum-assisted Moldingmentioning
confidence: 99%
“…In literature, several groups have successfully used anodized aluminum oxide (AAO) that under proper anodizing conditions contains very well structured nanopores as templates to fabricate nanoscale roughness [2][3][4][5][6][7][8][9]. With advances in polymer sciences and discovery of precursor wetting films [10], nanotubes and nanofibers have been successfully fabricated with several polymers [2][3][4][5][6][7][8][9][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] using methods often termed as "template synthesis" [31,32]. Detailed reviews can be found in [4,26,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%